Some Properties of the Beurling-Ahlfors Extension (Communications in Mathematical Research, 2021)
In this paper, we study the Beurling-Ahlfors extensions and prove tworesults. The first variation of the Beurling-Ahlfors extension is not always harmonic;the Beurling-Ahlfors extension of a quasi-symmetric mapping is not always harmonic.